LECTURER TALK IN THE EMI CLASSROOM: A SPEECH ACT ANALYSIS - Lestari, Sri; Mutiaraningrum, Ira (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2023)
Research in the area of utilizing English as a medium of instruction has overlooked the investigation of communication issues among lecturers teaching their disciplines in English. This study seeks to determine the most common speech act employed by lecturers utilizing English as a medium of instruction, the rationale behind the selection, and its implication on pedagogy and education. Employing a case study, we recruited four instructors from Biology and Primary Education who teach content-based subjects in English. With Searle's framework of speech acts, the study revealed that assertive speech acts were used 42.85%, directive 25.8%, expressive 21.65%, and commissive 9.6%. The findings indicate that most lecturers used assertive speech acts to clarify content and engage students in achieving learning objectives. This study expected to give contribution as reflection tool on how speech acts should be performed in teaching process to promote successful English utilization by instructors teaching non-English subjects.